Trudyashchiyesya sovetskogo soyuza! Krepite oboronu strany sovetov! - Klutsis, Gustav (OGIZ- IZOGIZ Gosudarstvennoe Izdatel'stvo Izobrazitel'nyh Iskusstv, 1933)
Red army soldier with masses of communist international in background and gas-mask wearing fascist monster Original title: Трудящиеся советского союза! Крепите оборону страны советов! Suggested translation: Workers of the Soviet Union! Strengthen the country's defense councils!; Item is framed; dimensions: 1455 X 1070 mm PO-2502